Potential of circular economy implementation in the mechatronics industry: An exploratory research. (1st December 2019) - Chouinard, Ugo; Pigosso, Daniela C.A.; McAloone, Tim C.; Baron, Luc; Achiche, Sofiane
Abstract: This paper investigates the current state of design in the mechatronic industry. First, based on a literature overview, key circular product characteristics are identified, namely modularity and robustness. Then, a survey has been distributed to practicing mechatronic engineers. Based on the survey, it is found that mechatronic systems are currently designed for long-term circular strategies, while the end-of-life is rarely considered. Furthermore, it is found that one issue in designing mechatronic devices is that they are prone to electronics obsolescence, and that safety regulations may prevent to design for circularity. Moreover, it is reported that customers do not currently require circular aspects in the mechatronic products and thus there is no incentive to designs according to circular principles. Finally, the paper discusses on new research ways of improving the circularity aspect of mechatronic devices, such as by facilitating remanufacturing or by using distributed system.